Depression and Rural Environment Are Associated With Poor Oral Health Among Pregnant Women in Northern Appalachia. (January 2016) - McNeil, Daniel W.; Hayes, Sarah E.; Randall, Cameron L.; Polk, Deborah E.; Neiswanger, Kathy; Shaffer, John R.; Weyant, Robert J.; Foxman, Betsy; Kao, Elizabeth; Crout, Richard J.; Chapman, Stella; Brown, Linda J.; et al.
Both oral health problems and depression among pregnant women contribute to maternal–infant health outcomes. Little is known, however, about the potential effects of clinically significant depression on the oral health status of pregnant women. The purpose of the present study was to determine the influence of clinically significant depression and rural- or urban-dwelling status on oral health outcomes among pregnant women. Pregnant women ( N = 685) in rural (i.e., West Virginia) and urban (i.e., Pittsburgh, PA) areas of northern Appalachia were assessed by calibrated examiners regarding gingivitis, oral hygiene, and DMFT (decayed, missing, and filled teeth), completed the Center for Epidemiologic Studies–Depression Scale (CES-D) and provided demographics. Participants were categorized based on clinically significant depressive symptoms (CES-D ≥ 16) and rural/urban domicile. Women with depression and those living in rural areas had worse oral health on all three indices than their non-depressed and urban counterparts. Depression, particularly among women in rural areas, affects certain oral health indices and represents a modifiable target for intervention. Moreover, treatments designed specifically for rural populations may be of particular utility. Women who are pregnant or planning to become pregnant may benefit from regular depression screenings from their dental and medical health care providers.